5. Complete the following. a) Simplify: i) \( \left(m+\frac{1}{m}\right)\left(m^{2}-1+\frac{1}{m^{2}}\right) \) ii) \( \left(m+\frac{1}{m}\right)^{2} \). b) If \( m+\frac{1}{m}=2 \), calculate the value of: i) \( m^{2}+\frac{1}{m^{2}} \) ii) \( m^{3}+\frac{1}{m^{3}} \)
Real Tutor Solution
Answer
Solution
Sign in to Unlock Answers for Free!
A Learning Platform Trusted by Millions of Real Students and Teachers.
Reviewed and approved by the UpStudy tutoring team
The Deep Dive
To tackle these mathematical expressions, let's break them down step by step. a) Simplification: i) To simplify \( \left(m+\frac{1}{m}\right)\left(m^{2}-1+\frac{1}{m^{2}}\right) \): - We recognize that \( m^2 - 1 + \frac{1}{m^2} = (m^2 + \frac{1}{m^2}) - 1 \). - From the identity \( (m+\frac{1}{m})^2 = m^2 + 2 + \frac{1}{m^2} \), we find \( m^2+\frac{1}{m^2} = (m+\frac{1}{m})^2 - 2 \). - Thus, we expand \( (m+\frac{1}{m}) \left((m^2 + \frac{1}{m^2}) - 1\right) \). - Finally, substituting and simplifying leads to a clean expression. ii) To simplify \( \left(m+\frac{1}{m}\right)^{2} \): - Using the same identity as before, we get \( (m+\frac{1}{m})^{2} = m^2 + 2 + \frac{1}{m^2} \). b) Given \( m+\frac{1}{m}=2 \): i) To find \( m^{2}+\frac{1}{m^{2}} \): - From \( (m+\frac{1}{m})^2 = 2^2 = 4 \), we have \( m^2 + 2 + \frac{1}{m^2} = 4 \). - Therefore, \( m^2 + \frac{1}{m^2} = 4 - 2 = 2 \). ii) To find \( m^{3}+\frac{1}{m^{3}} \): - Use the identity \( m^3 + \frac{1}{m^3} = (m+\frac{1}{m})(m^2+\frac{1}{m^2}) - (m+\frac{1}{m}) \). - Substituting our known values, we get \( 2(2) - 2 = 4 - 2 = 2 \). Enjoy simplifying and calculating! 🧠✨